+0  
 
0
213
2
avatar+2448 

Please help, ty!

 Apr 26, 2018
 #1
avatar+7352 
+1

\(\phantom{=\,}\dfrac{x^2+2x-24}{3x+18}\)

                                     Factor  x2 + 2x - 24  as  (x + 6)(x - 4) .

\(=\,\dfrac{(x+6)(x-4)}{3x+18}\)

                                     Factor  3  out of the denominator to get  3x + 18  =  3(x + 6) .

\(=\,\dfrac{(x+6)(x-4)}{3(x+6)}\)

                                     Reduce the fraction by  (x + 6)  and note that  x ≠ -6  .

 

\(=\,\dfrac{x-4}{3}\qquad\text{and}\qquad x\neq-6\)

.
 Apr 26, 2018
edited by hectictar  Apr 26, 2018
 #2
avatar+2448 
+1

Tysm I really appreciate your help!

RainbowPanda  Apr 26, 2018

26 Online Users

avatar
avatar